The Potential for Phospholipids in the Treatment of Airway Inflammation: An Unexplored Solution - Komalla, Varsha; Mehta, Meenu; Achi, Fatima; Dua, Kamal; Haghi, Mehra (Current Molecular Pharmacology, 2021)
Asthma, chronic obstructive pulmonary disease (COPD), and cystic fibrosis (CF) are major inflammatory respiratory diseases. Current mainstay therapy for asthma, and chronic obstructive pulmonary disease are corticosteroids, which have well-established side effect profiles. Phospholipids (PLs) are ubiquitous, diverse compounds with varying functions such as their structural role in the cell membrane, energy storage, and cell signaling. Recent advances in understanding PLs role as inflammatory mediators in the body as well as their widespread long-standing use as carrier molecules in drug delivery demonstrate the potential application of PLs in modulating inflammatory conditions. This review briefly explains the main mechanisms of inflammation in chronic respiratory diseases, current anti-inflammatory treatments and areas of unmet need. The structural features, roles of endogenous and exogenous phospholipids, including their use as pharmaceutical excipients, are reviewed. Current research on the immunomodulatory properties of PLs and their potential application in inflammatory diseases is the major section of this review. Considering the roles of PLs as inflammatory mediators and their safety profile established in pharmaceutical formulations, these small molecules demonstrate great potential as candidates in respiratory inflammation. Future studies need to focus on the immunomodulatory properties and the underlying mechanisms of PLs in respiratory inflammatory diseases.
Keywords: Phospholipids (PLs)